Clinical benefit of long-term use of dual antiplatelet therapy for acute myocardial infarction patients with the PEGASUS-TIMI 54 criteria - Lee, Kwan Yong; Hwang, Byung-Hee; Choo, Eun-Ho; Lim, Sungmin; Kim, Chan Jun; Kim, Jin-Jin; Byeon, Jaeho; Choi, Ik Jun; Oh, Gyu Chul; Choi, Yoon Seok; Yoo, Ki Dong; Chung, Wook Sung; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background We evaluated the effectiveness of extended dual antiplatelet therapy (DAPT) usage after 2nd-generation drug elution stent implantation in acute myocardial infarction (AMI) survivors with high ischemic risk characteristics who had no major bleeding for 24 months under at least 1 year of DAPT maintenance. Materials and methods The primary ischemic and bleeding endpoints were the risk of mortality and the risk of BARC 3 or 5 (major) bleeding. We investigated the event rates for 2–5 years after the index procedure. Results Of 3382 post-AMI survivors who met the PEGASUS-TIMI 54 (PEGASUS) criteria and without major bleeding until 2 years, 2281 (67.4%) maintained DAPT over 24 months, and 1101 (32.5%) switched DAPT to a single antiplatelet agent. The >24 M DAPT group showed a lower risk of mortality than the 12–24 M DAPT group (7.2 vs. 9.2%; adjusted hazard ratio: 0.648; 95% confidence interval: 0.595–0.976; p < 0.001). The mortality risk was significantly greater as the number of PEGASUS criteria increased (p < 0.001). DAPT > 24 months was not significantly associated with a decreased risk for major bleeding in the population meeting the PEGASUS criteria (2.0 vs. 1.1%; p = 0.093). The results were consistent after propensity-score matching and inverse probability weighting to adjust for baseline differences. Conclusion Extended DAPT over 24 months was associated with a lower risk of mortality without increasing the risk of major bleeding among 2 years survivors after AMI who met the PEGASUS criteria and had no major bleeding events before 24 months.